An analysis of Wi-Fi security vulnerabilities in Malaysia: A survey in Golden Triangle Kuala Lumpur - Sajat, M. S.; Hassan, Suhaidi; Chit, Suwannit Chareen (IEEE Computer Society, 2006)
The widespread use of Wi-Fi in the US and Europe has brought a new security concern among Wi-Fi owners and developers. However this concern and awareness are still low in Malaysia. A survey using the NetStumbler and a GPS receiver to locate the coordinates of detected Wi-Fi APs was carried out in the Golden Triangle area of Kuala Lumpur, Malaysia. This paper will describe how far the owners and administrators in Malaysia secure their Wi-Fi networks and subsequently create security awareness among Wi-Fi owners and administrators.